Estratégias para a superação de problemas locais à Vila do Abraão e sua relação com o desenvolvimento sustentável do turismo - Sampaio, Rafael Santos (2005)
This study evaluates how the interaction among organizations located in Vila do Abraão, in Ilha Grande, Rio de Janeiro State, has contributed to the sustainability of this locality. An analysis of the island¿s local problems showed that firms informality and solid waste management practices were bringing damaging consequences to the island, and that this local productive arrangement (APL) has been able to collectively find solutions to such issues. These solutions basically encompassed: a) choosing estrategies the lead to a self-sustained model and not traditional way dependent on tax benefits; b) recognizing that the solutions to these problems involved the common action of public and private sectors and the civil society, and that various artifices should be used to establish such cooperation; c) the presence of actors outside the APL who played an important role in overcoming the problems of the cluster; d) using transparent legal instruments that defined the rights and obligations of each party and e) tripartite social entrepreneurship actions through NGOs to help solve problems common to the whole island.